Whirling Dance as a Sufi Healing Method: A Phenomenological Study of the Sufi Dance Community in Surakarta - Pambuka, Fian Rizkyan Surya; Saifuddin, Ahmad (Teosofi: Jurnal Tasawuf dan Pemikiran Islam, 2023)
This study aimed to explain the dynamics of Sufi healing through Sufi dance. Using the qualitative approach through the phenomenology of religion, the data of the present study was collected by interviews, observations, and visual materials. The research sample consisted of five members of a Sufi dance group in Surakarta, who found relief from their physical and psychological ailments through the movements performed in the whirling dance training. The healing process of physical and psychological issues through the Sufi dance can be seen in the aspects of catharsis, breath management and regulation, cognitive restructuring, habituation mechanisms, self-control, and muscle stretching. However, the expression of these aspects in differed in each case. In addition, this study also found that ablution and prayer and the altered state of consciousness during the performance of the dance had an impact on the healing process. Therefore, Sufi dance should be included as an alternative healing method.